Investigations of thickness effects on the acoustic characteristics of symmetric and asymmetric airfoils. Issue 1 (March 2023) - Kumar, Sujit; Mishra, Priyanshu; Narayanan, S
The present paper provides a detailed acoustic characterization of symmetric and asymmetric NACA airfoils for various thickness ratios to determine the best thickness ratio and geometry which provide lower acoustic radiations with respect to the standard NACA0010 airfoil. The studies are conducted for various t/c values of 0.12, 0.15 and 0.21, where t is the airfoil thickness and c is the airfoil chord. The far-field acoustic emissions are observed to decrease with increase in t/c ratios for both the symmetric and asymmetric airfoils. For all the t/c values and jet velocities studied, the asymmetric airfoils show higher noise reductions from mid to high frequencies as compared to the symmetric ones, which might be due to the reduced transverse velocity fluctuations as a result of the large distortions imparted to oncoming turbulent gust by the formation of the larger stagnation pressure zone. The symmetric airfoils show a maximum reduction up to 3 dB from mid to high frequencies while asymmetric ones show a reduction up to about 5 dB. An empirical expression is developed for the ΔOAPWL as a function of t/c only for both the symmetric and asymmetric airfoils, where ΔOAPWL is the overall sound power reduction level in dB. It reveals that the ΔOAPWL follow a second order polynomial for both the symmetric and asymmetric airfoils at all jet velocities studied. It is observed that thicker (i.e., t/c = 0.21) symmetric and asymmetric airfoils show lower acoustic radiations as compared to the thinner ones for all the emission angles. In general, it is observed that the thinner airfoils show higher directivity as compared thicker ones, albeit they show a common trait of downstream directivity. Further the highest directivity is seen at an emission angle of 67.5° for both the symmetric and asymmetric airfoils. Thus, the present study clearly demonstrates that the airfoils with higher t/c ratios could be considered as the best passive means for achieving substantial reductions of airfoil broadband noise over a wide range of frequencies.